2016
DOI: 10.1037/apl0000131
|View full text |Cite
|
Sign up to set email alerts
|

Are organizational justice rules gendered? Reactions to men’s and women’s justice violations.

Abstract: Research has shown that gender role prescriptions can bias reactions to men's and women's work behaviors. The current work draws upon this idea and extends it to consider violations of procedural and interactional justice rules. The results of four experimental studies demonstrate that men and women receive differential performance evaluation ratings and reward recommendations when they violate those organizational justice rules that coincide with the content of prescriptive gender stereotypes. Specifically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 65 publications
3
52
1
1
Order By: Relevance
“…Although past research has found measures of performance and rewards to adequately capture reactions to norm-violating women (Caleo, 2016;Heilman & Chen, 2005), measures that are more proximally related to gender norm violation offer a closer route through which to test the current ideas. A second study was conducted to address this option.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although past research has found measures of performance and rewards to adequately capture reactions to norm-violating women (Caleo, 2016;Heilman & Chen, 2005), measures that are more proximally related to gender norm violation offer a closer route through which to test the current ideas. A second study was conducted to address this option.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is possible that the dependent measures used in Study 1 failed to capture sufficient movement for women because they are closely aligned with success, an outcome that is tied to male stereotypes of agency (Abele, ). Although past research has found measures of performance and rewards to adequately capture reactions to norm‐violating women (Caleo, ; Heilman & Chen, ), measures that are more proximally related to gender norm violation offer a closer route through which to test the current ideas. A second study was conducted to address this option.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations